Integrating Sharia Literacy and Digital Philanthropy Amidst the FoMO Phenomenon - Amry Abdurrahman; M. Kholid; Ulya Dharodjah (STAI Syaichona Moh. Cholil Bangkalan, 2026)
The era of financial digitalization triggers behavioral pathologies among Muslim Generation Z through Fear of Missing Out (FoMO), driving impulsive consumption (israf). While existing literature narrowly positions Sharia financial literacy as a passive, theoretical cognitive instrument, this study aims to conceptualize the active moderating roles of Sharia financial literacy and digital philanthropy in mitigating these algorithm-driven distortions. Employing a Qualitative Systematic Literature Review (SLR) via the PRISMA protocol, 24 peer-reviewed articles (2019–2025) were analyzed from Google Scholar, Crossref, and Dimensions using Publish or Perish. The primary novelty of this study lies in its theoretical synthesis, introducing the